Effect of Cd on cation redistribution and order-disorder transition in Cu2(Zn, Cd)SnS4. Issue 47 (20th November 2019) - Hadke, Shreyash; Chen, Wei; Tan, Joel Ming Rui; Guc, Maxim; Izquierdo-Roca, Victor; Rignanese, Gian-Marco; Hautier, Geoffroy; Wong, Lydia Helena
Abstract : The difference in the order-disorder transformation leads to a reduction in atomic disorder in Cu2 CdSnS4 as compared to Cu2 ZnSnS4 . Abstract : Cation substitution has been extensively used to improve the fundamental optoelectronic properties and the photovoltaic performance of kesterite solar cells, and some of the most promising results have been obtained by substituting zinc with cadmium. Structurally, the positive effects of Cd have been attributed to the expected increase in the formation energy of defects such as CuZn + ZnCu due to the larger ionic radius of Cd 2+ as compared to Zn 2+ . However, ab initio calculations using density functional theory (DFT) showed similar formation energies for CuZn + ZnCu in Cu2 ZnSnS4 and CuCd + CdCu in Cu2 CdSnS4 . Further, in this report, it is shown that Cd does not directly substitute the zinc lattice sites (2d Wyckoff positions) in the Cu2 ZnSnS4 structure, but rather, a two-way cation restructuring due to the continuous transformation of the structure from kesterite to stannite leads to Cu replacing Zn, and Cd occupying the Cu sites (2a Wyckoff positions) in the partially Cd-substituted Cu2 Zn1− x Cd x SnS4 . Hence, the structural reasons for the beneficial effects of Cd need to be reinterpreted. Here, using computational model based on cluster expansion (fitted on DFT data), Monte-Carlo simulations, and differential scanning calorimetry, it is shown that Cu2 CdSnS4 has less structural disorder than Cu2 ZnSnS4 even if the thermodynamic point defect formation energy calculated using diluted point-defect models for disorder-inducing CuZn + ZnCu and CuCd + CdCu defects in these two materials is predicted to be similar. This difference in the structural disorder is due to a sharp order-disorder transformation in Cu2 ZnSnS4 at about 530 K, and a continuous order-disorder transformation in Cu2 CdSnS4 throughout the range of processing temperatures.